Formulation of Distinction-Based MBKM Design Sharia Economics Study Program (Mapping Study of Potential Partner Institutions of UIN Prof. K.H. Saifuddin Zuhri Purwokerto) - Dewi Laela Hilyatin; Tri Mulatsih Pudjileksani; Gebyar Cahya Aditya; John Paul Banac; Sugeng Riyadi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This research, titled